Perceived Benefits of Oral Presentations in Helping Students Improve Their Confidence in Speaking - Ismail, Nathasa Al Maidah; Jaya, Hariswan Putera (Universitas Pahlawan Tuanku Tambusai, 2026)
Oral presentations are often used in English courses to improve speaking skills. However, there is still little research about how students see their benefits in building speaking confidence, especially in university settings. This study aims to explore university students’ perceptions of the benefits of oral presentations in English classes. Even though oral presentations can help improve speaking skills, many students still face challenges such as low confidence, anxiety, limited vocabulary, and difficulty in organizing ideas. This research used a descriptive qualitative method with interviews, observations, and documentation as the main data sources. The data were analyzed using thematic analysis to find common patterns. The results show that the main factors affecting students’ oral presentations are speaking anxiety, lack of vocabulary, little experience in public speaking, and fear of making mistakes. To deal with these problems, students used strategies such as repeated practice, using media, managing time, and getting support from lecturers and peers. This study shows the importance of oral presentations in developing speaking confidence and suggests that teachers need to provide better strategies to support students in English learning.